Novel polymorphisms and genetic studies of the shadow of prion protein gene (SPRN) in pheasants - Choi, Da-In; Zayed, Mohammed; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2024)
Background: Prion diseases in mammals are caused by the structural conversion of the natural prion protein (PrP C ) to a pathogenic isoform, the "scrapie form of prion protein (PrP Sc )". Several studies reported that the shadow of prion protein (Sho), encoded by the shadow of prion protein gene (SPRN), is involved in prion disease development by accelerating the conformational conversion of PrP C to PrP Sc . Until now, genetic polymorphisms of the SPRN gene and the protein structure of Sho related to fragility to prion disease have not been investigated in pheasants, which are a species of poultry.Methods: Here, we identified the SPRN gene sequence by polymerase chain reaction (PCR) and compared the SPRN gene and Sho protein sequences among various prion diseasesusceptible and -resistant species to identify the distinctive genetic features of pheasant Sho using Clustal Omega. In addition, we investigated genetic polymorphisms of the SPRN gene in pheasants and analyzed genotype, allele, and haplotype frequencies, as well as linkage disequilibrium among the genetic polymorphisms. Furthermore, we used in silico programs, namely Mutpred2, MUpro and AMYCO, to investigate the effect of non-synonymous single nucleotide polymorphisms (SNPs). Finally, the predicted secondary and tertiary structures of Sho proteins from various species were analyzed by Alphafold2.In the present study, we reported pheasant SPRN gene sequences for the first time and identified a total of 14 novel SNPs, including 7 non-synonymous and 4 synonymous SNPs. In addition, the pheasant Sho protein sequence showed 100% identity with the chicken Sho protein sequence. Furthermore, amino acid substitutions were predicted to affect the hydrogen bond distribution in the 3D structure of the pheasant Sho protein.To the best of our knowledge, this is the first report of the genetic and structural features of the pheasant SPRN gene.